The haloarchaeal MCM proteins: bioinformatic analysis and targeted mutagenesis of the β7-β8 and β9-β10 hairpin loops and conserved zinc binding domain cysteines - Kristensen, Tatjana P.; Maria Cherian, Reeja; Gray, Fiona C.; MacNeill, Stuart A. (Frontiers in Microbiology, 2014)
The hexameric MCM complex is the catalytic core of the replicative helicase in eukaryotic and archaeal cells. Here we describe the first in vivo analysis of archaeal MCM protein structure and function relationships using the genetically tractable haloarchaeon Haloferax volcanii as a model system. Hfx. volcanii encodes a single MCM protein that is part of the previously identified core group of haloarchaeal MCM proteins. Three structural features of the N-terminal domain of the Hfx. volcanii MCM protein were targeted for mutagenesis: the β7-β8 and β9-β10 β-hairpin loops and putative zinc binding domain. Five strains carrying single point mutations in the β7-β8 β-hairpin loop were constructed, none of which displayed impaired cell growth under normal conditions or when treated with the DNA damaging agent mitomycin C. However, short sequence deletions within the β7-β8 β-hairpin were not tolerated and neither was replacement of the highly conserved residue glutamate 187 with alanine. Six strains carrying paired alanine substitutions within the β9-β10 β-hairpin loop were constructed, leading to the conclusion that no individual amino acid within that hairpin loop is absolutely required for MCM function, although one of the mutant strains displays greatly enhanced sensitivity to mitomycin C. Deletions of two or four amino acids from the β9-β10 β-hairpin were tolerated but mutants carrying larger deletions were inviable. Similarly, it was not possible to construct mutants in which any of the conserved zinc binding cysteines was replaced with alanine, underlining the likely importance of zinc binding for MCM function. The results of these studies demonstrate the feasibility of using Hfx. volcanii as a model system for reverse genetic analysis of archaeal MCM protein function and provide important confirmation of the in vivo importance of conserved structural features identified by previous bioinformatic, biochemical and structural studies.